PT ZYX operation team acidizing-solvent stimulation candidate process improvement lean sigma - Nurbatin, Ahmad (2014)
In this paper the main focus is how to determine candidate stimulation program that is easy and fast with optimal gain.There are any initiative to conducted many process improvements since 2000 is to do trial and error to total usage of chemical used, fix standard operating procedures stimulation job.Process improvement is done only focuses on the dominant factor without doing a review of other parameters such as fluid flow, temperature and water cut.A lean sigma project that was initiated in 2004 standardized the Simple Acidizing (stimulation) process, including the Well Selection Criteria. This revised process improved the job success rate of Simple Acidizing jobs as well as increased the average oil gain per job associated with Simple Acid efforts.By continue using lean sigma method, the team conducted a review using data on wells stimulation ever undertaken in the previous year, so we get a baseline and stimulation program that generates large oil gain. Stimulation of the review of data, there are four parameters that affect the measured gain obtained oil. All 4 of these parameters is the decline fluid, water cut, wellhead temperature and scaling index. Each data obtained in accordance with the given score gains generated so by merging all 4 of these parameters will result in oil optimum gain. The improvement in the method of selecting candidate wells will allow employees to do the job seeking candidate’s stimulation.